Thealogy Matters. (September 2019) - Christ, Carol P.
In this article Carol P. Christ states that 'thealogy matters' because religious symbols not only articulate meaning but also provide orientation for ethical decision-making. Rejecting the notions that religious meaning is delivered from on high and that traditions must be uncritically accepted, she proposes a model of 'embodied theology' in which individuals and communities take responsibility for religious worldviews. She asks us to question Jungian theories of the feminine, images of the Goddess in patriarchal traditions, models of ritual practice in the Wiccan tradition as articulated by Gerald Garner, and the idea of divine omnipotence modelled on the 'tyrant ideal' of God. She explores two ways in which process panentheism can help us to understand the divine power we call Goddess.